Pengaruh Disiplin terhadap Kinerja Karyawan pada Rumah Sakit Tk. IV DR. Bratanata Jambi - Agung Aditia Pratama (Science of Management and Students Research Journal (SMS), 2021)
With the hope that the results of work with a desire so that it has an impact on improving work performance.  Therefore, coaching and development of employee performance is treated effectively in order to achieve a smooth process of activities in an organization that will come.  The research variable is work discipline on employee performance.  The research population is hospital employees dr.  Bratanata Jambi.  Slovin sampling method.  Samples were taken 100 people.  The research instrument used a questionnaire containing 18 items. The research method was carried out using a simple linear regression analysis tool with the help of SPSS 20. The test carried out was a hypothesis test, namely test and to find out how much the coefficient of determination (R2) was, based on the results of this study that partially  service quality has a significant effect on patient satisfaction because the count is greater than t table of 3.190 > 0.196, so it can be said that there is a positive effect.  The coefficient of determination is 9.4% while the remaining 90.6% is influenced by other variables.  This means that work discipline has a positive and significant effect on employee performance at the hospital, dr.  Bratanata Jambi.  The result of the simple linear regression analysis is Y = 23.766 + 0.317 X+e